2020
DOI: 10.1186/s13048-020-00700-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting complete cytoreduction for advanced ovarian cancer patients using nearest-neighbor models

Abstract: Background The foundation of modern ovarian cancer care is cytoreductive surgery to remove all macroscopic disease (R0). Identification of R0 resection patients may help individualise treatment. Machine learning and AI have been shown to be effective systems for classification and prediction. For a disease as heterogenous as ovarian cancer, they could potentially outperform conventional predictive algorithms for routine clinical use. We investigated the performance of an AI system, the k-nearest neighbor (k-NN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…The CT model of this study yielded an accuracy of 69.4% and an ROC area of 0.635, indicating a poor discrimination ability for differentiating the result of cytoreduction status. Similar results have been proposed by Liaos et al [ 23 ], with an accuracy of 66% for predicting complete cytoreduction of advanced ovarian cancer patients using nearest-neighbor models with attributes including clinical data and CT findings. Other studies showed a low sensitivity (27%) but high specificity (91%) for predicting incomplete or suboptimal cytoreduction using CT-PCI.…”
Section: Discussionsupporting
confidence: 82%
“…The CT model of this study yielded an accuracy of 69.4% and an ROC area of 0.635, indicating a poor discrimination ability for differentiating the result of cytoreduction status. Similar results have been proposed by Liaos et al [ 23 ], with an accuracy of 66% for predicting complete cytoreduction of advanced ovarian cancer patients using nearest-neighbor models with attributes including clinical data and CT findings. Other studies showed a low sensitivity (27%) but high specificity (91%) for predicting incomplete or suboptimal cytoreduction using CT-PCI.…”
Section: Discussionsupporting
confidence: 82%
“…Developing methods to predict surgical outcomes is important to identify who will benefit from maximal cytoreductive effort in the primary or interval surgical setting. Data mining technologies appear to be promising for non-invasive, clinically meaningful improvements in the prediction accuracy of pre-surgical patient selection [35]. Although this approach may not be yet validated in ovarian cancer, it has the potential to be more reflective than other intra-operative assessments such as the PCI index.…”
Section: Discussionmentioning
confidence: 99%
“… 10 We previously demonstrated the feasibility of using a ML approach, the k-NN model, which is very much reflective of ‘previous clinical experience’ for accurate prediction of complete cytoreduction in advanced-stage HGSOC surgery. 11 …”
Section: Introductionmentioning
confidence: 99%